2018
DOI: 10.1021/acs.energyfuels.7b03516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Salinity and Mineralogy on Slick Water Spontaneous Imbibition and Formation Strength in Shale

Abstract: Spontaneous imbibition is one of the mechanisms proposed to reveal the fate of fluids used during fracturing operations in shale reservoirs. However, the influence of salinity and mineralogy on the imbibition kinetics is not yet well understood. We performed imbibition experiments on samples collected from Woodford and Caney shale outcrops with slick water having salinities up to 15 wt % KCl. The impact of salinity on the imbibition rate and capacity shows a different trend for samples of varying mineralogy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…A similar inverse correlation was observed at 0.1‐M concentration (K + < Na + < Ca 2+ < Mg 2+ ) except that K + uptake was lower than that of Na + . The nonmonotonous behavior of K + has been observed previously (Biaeopiotrowicz et al, ; Mehana et al, ; Puntervold et al, ). The reason for this exceptional behavior is that K + has swelling inhibiting characteristics due to its versatile hydration and leachability properties.…”
Section: Resultssupporting
confidence: 68%
“…A similar inverse correlation was observed at 0.1‐M concentration (K + < Na + < Ca 2+ < Mg 2+ ) except that K + uptake was lower than that of Na + . The nonmonotonous behavior of K + has been observed previously (Biaeopiotrowicz et al, ; Mehana et al, ; Puntervold et al, ). The reason for this exceptional behavior is that K + has swelling inhibiting characteristics due to its versatile hydration and leachability properties.…”
Section: Resultssupporting
confidence: 68%
“…Wettability and oil viscosity are considered as the major influencing factors, and thus oil recovery from the reservoir they were studying could be improved by injecting steam, low-salinity water, and surfactant [29]. It has also been proposed that factors impacting the recovery efficiency of tight reservoirs are: wettability > brine, and salinity > residual oil saturation [30][31][32][33]. Ali Habibi et al suggested that the position for imbibition is random inside the same core, and that by soaking the core sample in brine solution the affinity between rock and fluids can be promoted, which further affects the wettability [34].…”
Section: Introductionmentioning
confidence: 99%
“…Gao and Hu (2016) tested samples on balance in directions parallel and transverse to the lamination and in imbibing fluids of deionized water and n-decane to investigate the influence of shale layers. Mehana et al (2018) The movement of imbibition front and the relationship between water loss and fracture aperture (Roychaudhuri et al, 2013).…”
Section: Balance-weighting Methodsmentioning
confidence: 99%